An analysis of the recori) of patients with sexually t ransmitted dlseases in reference health clinics in Fortaleza, Brasil, in 2000 and 2001 - Araújo, Maria A.L.; Bucher, Júlia S.N.F.; Bello, Pierre Y. (Brazilian Journal of Sexually Transmitted Diseases, 2002)
Fundamentais: Starting from the knowledge of the social, demographic. clinicai profilc and patients’ behaviour assisled with sexually transmitted discase (STD) in units of reference. it is possible to develop an educacional work gone back lo lhat demand. Objectivc: To contribute for the improvement of the offer to the Services of STD. offering aclions. especially the counselling in agreement with the characteristics of the assisted population. Methodology: The study consisted if the data collecting from the 306 patients’ records assisted with STD in four units of reference in Fortaleza city, throughout May 2000 to April 2001; These units are two centers of heallh (C.S. Carlos Ribeiro and C.S. Anastácio Magalhães) and two hospitais ( N. Sr° da Conceição and Gonzaga Mota de Messejana) and they are part of the projcct DST/HIV. that worked in the structuring of a reference net for STD in the State of Ceará. The analysis was conducted using Epi-lnfo 6.04c. Results: The findings show us a demand formed by young adults (50.4%) and with good educational background (74,1%). The men are self-medicated more before seeking the unit (p<0,0001: OR = 3.2: IC ai 95%: 1.6-6.3) and they refer more sexual partners than lhe women (p<0,00001; OR = 9.7: IC at 95%: 4.6-20.8). Almost all women assisted with STD referred only a sexual partner in the last three months previous to the consultation (appointment). Conclusion: It is necessary to incorporate to the content of lhe counselling for STD strategies that seek the self-care and promote the patients' health.